(untitled) (Third Sector Social Economic Review, 2014)
The aim of this research is to examine the problems faced by administrators of boarding schools during school management.In this research, the relationship between the school administrators and their inferiors/superiors, the problems they faced with, the schools’ opportunities and demographic information of the administrators all around Turkey are analyzed.The questionnaires are conducted to 85 of 539 boarding schools in Turkey. The questionnaires are just for the administrators. The data of the research is gained by literature review and questionnaire method.The most important problem faced by administrators of boarding schools is being lack of scientific information about management. Additionally it is found out that the number of in-service educational activities about management given to administrators by Ministry of National Education must be increased.